The role of the Financial and Administrative Control Bureau in maintaining financial discipline in Bahraini legislation - Aljabali, Nadya Esmail Mohmmed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study targets the basic tasks of the Office of Financial and Administrative Supervision, which is to preserve public money from extravagance, theft and lack of commitment to financial discipline, and we used the method of the analytical approach to describe aspects of the issue and discuss its problems and analyze them in legal analysis by reviewing the texts of the Constitution and the Law of the Office of Supervision.This study necessitated knowing the organization of the Office of Supervision, its objectives and its relationship with the legislative and executive authority, as well as the independence that it enjoys, whether from a financial or administrative point of view, which the Constitution and the Bureau's law granted to it in order to exercise its duties in full freedom and transparency without any restrictions or pressure from any party. The Bureau is considered as a partner to the legislative authority and the government through the annual report it submits to them for financial discipline, especially in light of the scarcity of financial and economic resources available to meet the needs of economic and social development, which requires serious attention to the development of the Bureau of Supervision.The study reached some recommendations that the Bahraini legislator should intervene with in order to reformulate or amend some legal articles, such as adding a new text that gives the Bureau to conduct previous control over the bodies subject to its control, as well as establishing a court for public funds in order to look into all problems and disputes related to public funds, in addition to the necessity of issuing the executive regulations for the SAI law so that the debts can fully carry out its duties in protecting public funds.
Keywords: Audit Bureau; independence; reports; public money; financial discipline